REFLECTION ON CITIZENSHIP, ETHICS, AND SPIRITUALITY THROUGH THE FILM THE BOY WHO HARNESSED THE WIND - de Paula, Maura Sousa da Silva; Azevedo , Leandra Martins de; Velasco , Maria Eduarda Santos; Cintra, Thauane Raissa Silva; Paula, Maura Sousa da Silva de (CIPEEX, 2025)
This report describes the experience lived by the students in the course Citizenship, Ethics, and Spirituality, offered in the Administration program at Universidade Evangélica de Goiás - Campus Rubiataba, during the 2nd semester of 2024. The activity was designed with the purpose of fostering critical reflection and civic formation through the analysis of the film The Boy Who Harnessed the Wind (2019), directed by Chiwetel Ejiofor, which depicts the trajectory of William Kamkwamba, a young Malawian who, in the face of extreme poverty and food insecurity, used education and innovation to build a wind turbine capable of transforming the reality of his community. The activity was carried out through collective planning by the students, the film screening, and discussions that allowed the exploration of the values conveyed by the narrative. The conduction of the activity was based on active learning, which encouraged dialogue, cooperation, and the joint construction of knowledge. During the process, challenges related to interpreting the central message arose, which were overcome through the alignment of ideas and collaboration among the participants. The analysis highlighted education as a tool for emancipation, ethics as a foundation for responsible decision-making, and spirituality as a source of hope and resilience in the face of adversity. When applied to social reality, these elements proved capable of promoting significant changes, strengthening active citizenship, and fostering collective responsibility. It is concluded that the experience provided integration between theory and practice, broadened the students’ critical perspective, and consolidated their identity as future professionals committed to social justice and community transformation.